CREDIT BANKING IN BUSINESS LAW PERSPECTIVE - Lukmanul Hakim (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
The purpose of this study is to encourage an increase in community prosperity, especially in banking legal aspects that can be seen by several things including credit agreements made by banking institutions and customers. In addition, the existence of business risk management has made banking institutions safeguard the health level of the bank so that people continue to believe in the existence of banking institutions. The method in this study uses qualitative analysis which will be given conclusions in accordance with the identification of problems. The results of this study conclude that credit is given to banking institutions in the perspective of business law by using credit agreements as risk mitigation so that non-performing loans will occur which will lead to a decline in bank soundness and the implementation of banking risk management from the perspective of current business law the bank's prudential principle by establishing management operational standards so that banks avoid business risks. The conclusion of this study is that banking institutions must implement procedures in accordance with the standards of each bank so that there will be no legal problems or other business risks. In addition, the application of the precautionary principle must always be applied considering one banking principle is the principle of caution. Tujuan penelitian ini adalah mendorong peningkatan kemakmuran masyarakat terutama dalam aspek hukum perbankan yang dapat terlihat dengan adanya beberapa hal diantaranya adalah perjanjian kredit yang dibuat oleh lembaga perbankan dan nasabah. Selain itu adanya manajemen risiko bisnis menjadikan lembaga perbankan lebih menjaga tingkat kesehatan bank agar masyarakat tetap percaya akan adanya lembaga perbankan. Metode dalam penelitian ini menggunakan analisis kualitatif yang akan diberikan kesimpulan yang sesuai dengan identifikasi permasalahan. Hasil penelitian ini menyimpulkan mengenai kredit diberikan kepada lembaga perbankan dalam perspektif hukum bisnis dengan menggunakan perjanjian kredit sebagai mitigasi risiko agar tidak terjadi kredit bermasalah yang akan mengakibatkan tingkat kesehatan bank menurun dan serta penerapan manajemen risiko bisnis lembaga perbankan ditinjau dari perspektif hukum bisnis saat ini dengan menerapkan prinsip kehati-hatian bank dengan membuat standar operasional manajemen sehingga bank terhindar dari risiko bisnis. Simpulan dari penelitian ini adalah lembaga perbankan harus menerapkan prosedur sesuai dengan standar dari masing-masing bank sehingga tidak akan terjadi masalah hukum atau risiko bisnis lainnya selain itu penerapan prinsip kehati-hatian harus selalu diterapkan mengingat salah satu azas perbankan adalah adanya Azas kehati-hatian.